2017
DOI: 10.1363/psrh.12021
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Family Planning Clinic–Based Partner Violence and Reproductive Coercion Intervention: Provider and Patient Perspectives

Abstract: Context Despite multiple calls for clinic-based services to identify and support women victimized by partner violence, screening remains uncommon in family planning clinics. Furthermore, traditional screening, based on disclosure of violence, may miss women who fear reporting their experiences. Strategies that are sensitive to the signs, symptoms and impact of trauma require exploration. Methods In 2011, as part of a cluster randomized controlled trial, staff at 11 Pennsylvania family planning clinics were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 57 publications
(81 reference statements)
1
52
0
Order By: Relevance
“…Research has found that reproductive coercion may be indicated by a woman’s repeated requests for pregnancy testing, emergency contraception, and sexually transmitted infection (STI) testing (Kazmerski et al, 2015; Miller & Silverman, 2010), and routine screening for reproductive coercion is recommended within health care settings (American College of Obstetricians and Gynecologists, 2013; Grace & Anderson, 2016; Miller et al, 2011, 2017). Regardless of whether a woman discloses this particular form of abuse, health care providers can educate clients about reproductive coercion as well as female-controlled contraception (Dutton et al, 2015; Miller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that reproductive coercion may be indicated by a woman’s repeated requests for pregnancy testing, emergency contraception, and sexually transmitted infection (STI) testing (Kazmerski et al, 2015; Miller & Silverman, 2010), and routine screening for reproductive coercion is recommended within health care settings (American College of Obstetricians and Gynecologists, 2013; Grace & Anderson, 2016; Miller et al, 2011, 2017). Regardless of whether a woman discloses this particular form of abuse, health care providers can educate clients about reproductive coercion as well as female-controlled contraception (Dutton et al, 2015; Miller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first such study worldwide; there is a lack of qualitative research on reproductive coercion in general, with a particular dearth around how reproductive coercion is understood and conceptualized. No studies have explored the views of health practitioners, other than in the context of evaluating specific interventions (Miller et al, 2017). Given the key role that health practitioners can play in identifying and responding to reproductive coercion (Grace, 2016), the lack of attention paid to their perceptions has been a significant oversight to date.…”
Section: Discussionmentioning
confidence: 99%
“…Although evaluation was limited and it was not always clear how, or if, this led to changes in the services provided, there was some evidence that this was perceived positively by professionals, resulting in substantial increases in the numbers of children screened at intake by child welfare and mental health professionals [31,32]. While this mainly positive evaluation mirrors the findings from trauma-informed screening/assessment initiatives in health services [43,44,45], implementation challenges were also noted with regard to IT systems, local culture, limited buy-in and the availability of evidence-based treatment. The importance of winning “hearts and minds” is evident in the wider TIC literature with some routine inquiry initiatives failing due to uncertainties about the benefits of screening, lack of clarity about how to use the information and respond to disclosures and concerns regarding a lack of availability of services for onward referral [46].…”
Section: Discussionmentioning
confidence: 99%